Pelatihan Public Speaking sebagai Upaya Pemberdayaan Ibu PKK Desa Purworejo Kecamatan Negeri Katon Pesawaran - Fihartini, Yuniarti; Huzaimah, RA. Fiska; Ambarwati, Dwi Asri Siti; Putra, Joni; Putri, Lidya Ayuni (Jurnal Pemberdayaan Ekonomi, 2024)
Purpose:  The purpose of this community service was to empower women, specifically the members of PKK Desa Purworejo, Kecamatan Negeri Katon, and Pesawaran, by enhancing their public speaking skills. The program aimed to improve students’ knowledge, confidence, and ability to speak effectively in public, enabling them to play a more significant role in their community. Methodology:  The service was conducted in Desa Purworejo, Kecamatan Negeri Katon, Pesawaran, and involved 30 participants from the local PKK organization. Training was facilitated by a team from the Faculty of Economics and Business at Universitas Lampung. The methodology included lectures, discussions, and practical exercises for public-speaking techniques. To evaluate the effectiveness of the training, pre- and post-test assessments were administered to measure the participants' improvement in knowledge and skills. Results:  The results of the pre- and post-test evaluations indicated a significant increase in the participants' public speaking abilities. The average pre-test score was 54.83, which improved to 81.5 in the post-test, reflecting an average increase of 26.67 points. Participants not only gained a better understanding of effective communication techniques but also demonstrated increased confidence in applying these skills in practice. Limitations: The program was limited by the small number of participants (30) and its short duration, which may have impacted the long-term retention and application of skills. Contribution: The training program successfully enhanced the participants’ public speaking skills, contributing to their empowerment as active community members. The involvement of local partners and a tailored approach to the community's needs were key factors in the programme’s success. This initiative highlights the potential for expanding similar programs to other communities, promoting sustainable empowerment for women across the region.